Prospective and Mental Change in Decision-Making in Critical Scenarios of Organizations (Review Article) - D. Vallejo; L. Sanandrés; V. Ruiz (ESPOCH Congresses)
We understand from the study of neuroscience that our mind has the power to change according to the social and cultural context in which we operate. The purpose of this research was to present epistemological theory, its importance in influencing decision-making, and strategic approaches from the perspective of complexity and neuroscience. For this, an in-depth bibliographic review was carried out based on the epistemological point of view and critical reading of published articles. The results demonstrated considerations about the presence of multiple philosophical traditions in the scientific process; the role of leadership and neuroscience as the axis of knowledge and their value for decision-making; and how, based on the paradigmatic dialectic, a new mental model and innovative foresight are useful for understanding the structures that require new models of planning for the future where possible and desirable. Thus, we conclude that a change of mentality to a new philosophy of interpretation of reality is important for the complexity of the construction of the future.